Health System Factors Influencing the Adoption and Sustainability of Evidence-Based Retinal Care Guidelines: A Systematic Review and Meta-Synthesis - Ramzi Amin; Rafika (HM Publisher, 2025)
Evidence-based guidelines (EBGs) are crucial for optimizing care and outcomes for highly prevalent retinal diseases like diabetic retinopathy (DR), age-related macular degeneration (AMD), and retinopathy of prematurity (ROP). However, their translation into routine clinical practice remains inconsistent. Understanding the health system factors that facilitate or impede the adoption and long-term sustainability of these guidelines is critical for improving population eye health. This systematic review and meta-synthesis aimed to identify and synthesize qualitative evidence on health system-level determinants influencing the implementation of retinal care EBGs. We conducted a systematic review following PRISMA guidelines. Major biomedical databases (PubMed, Scopus, Embase, Web of Science) and grey literature sources were searched from January 2013 to December 2024 using keywords related to retinal diseases, guidelines, implementation, adoption, sustainability, and health systems. Inclusion criteria focused on qualitative or mixed-methods studies exploring factors influencing the uptake or continued use of formal retinal care guidelines within clinical settings. Two reviewers independently screened titles/abstracts and full texts, extracted data, and assessed study quality using the Critical Appraisal Skills Programme (CASP) Qualitative Checklist. A thematic synthesis approach, following Noblit and Hare's methodology for meta-ethnography, was employed to synthesize findings across studies, involving familiarization, coding, theme generation, and synthesizing translations between studies. 7 studies met the inclusion criteria. These studies originated from diverse healthcare systems and focused primarily on DR and AMD guidelines. Quality assessment indicated moderate to high methodological rigor across the included studies. The meta-synthesis identified six interconnected key themes representing health system factors influencing guideline adoption and sustainability: leadership engagement and organizational culture prioritizing evidence-based practice; resource allocation and infrastructure adequacy, including staffing, funding, and integrated IT systems; inter-professional collaboration and streamlined communication pathways across disciplines and care settings; alignment with external policy levers and financial incentives; perceived guideline characteristics and adaptability within local workflows; and robust feedback mechanisms and continuous quality improvement cycles integrated into the system. Lack of resources, fragmented communication, conflicting financial incentives, and inadequate leadership support emerged as primary barriers. In conclusion, the successful adoption and sustainability of evidence-based retinal care guidelines are profoundly influenced by a complex interplay of health system factors. Effective implementation requires more than guideline dissemination. Addressing these system-level determinants is paramount for bridging the evidence-practice gap and reducing preventable vision loss from retinal diseases globally. Policymakers and healthcare administrators must consider these multifaceted factors when designing and implementing strategies to enhance retinal care quality.